Design And Analysis Of Triangular Array Antenna For Uhf Rfid Reader - Muhammad Firdaus, Zawawi (2022)
In this paper, the purpose of this study is to design and analysis the triangular array microstrip patch antenna for application of Radio Frequency (RFID) Ultra High Frequency (UHF). RFID is a technology that uses of radio waves automatically identify and read information from tag with distance. The patch design on this project consists of triangular patch with array. Array antennas are used in RFID application as it offers high gain and directivity to allow a long distance read range. The microstrip patch is arranged in 2 x 1 array and material used is FR-4 with dielectric constant 4.7 with height of 0.16 cm. The material for patch is copper with height 0.035 mm and used to design triangular shape. Design of antenna patch 919MHz to 923MHz is designed, built, and measured for UHF RFID application in Malaysia. Parametric theory and calculation studies are conducted to analysis changes in operations in radio frequency identification (RFID) application (UHF). The antenna simulation was run using the CST Studio Suite 2019 as the primary software to model and simulate the results, there are a few parameters that going to be analyses which includes reflection coefficient (S11), Voltage Standing Ratio (VSWR), directivity, gain, radiation pattern and bandwidth.